Racial Heteroidentification Committees In Brazil: Reflections on Self-Identification And Self-Declaration (Global Journal of Human-Social Science, 2023)
We intend to discuss the heteroidentification committees in competition for racial quotas for black people to ingress in a public university in Brazilian Higher Education. Firstly, we begin with a brief presentation of this educational system and the context of the affirmative action policy in racial markers in Brazil. Secondly, we introduce the conceptual differentiation between "self-identification" (of the dimension of 'to be') and "self-declaration" (of the dimension of 'to do'). Thirdly, we present Brazil's socio-legal context of racial affirmative action policies. Finally, we argue that the result of heteroidentification committees does not invalidate racial selfidentifications but only self-declarations. That procedure is an essential method of social control of the public policy of racial affirmative actions in Brazilian Higher Education.
Keywords: brazilian higher education racial heteroidentification committees self-identification selfdeclaration